Strategic Purchasing: The Neglected Health Financing Function for Pursuing Universal Health Coverage in Low- and Middle-Income Countries; Comment on "What's Needed to Develop Strategic Purchasing in Healthcare? Policy Lessons from a Realist Review" - Kara Hanson; Edwine Barasa; Ayako Honda; Warisa Panichkriangkrai; Walaiporn Patcharanarumol (Kerman University of Medical Sciences, 2019)
Sanderson et al's realist review of strategic purchasing identifies insights from two strands of theory: the economics of organisation and inter-organisational relationships. Our findings from a programme of research conducted by the RESYST (Resilient and Responsive Health Systems) consortium in seven countries echo these results, and add to them the crucial area of organisational capacity to implement complex reforms. We identify key areas for policy development. These are the need for: (1) a policy design with clearly delineated responsibilities; (2) a task network of organisations to engage in the broad set of functions needed; (3) more effective means of engaging with populations; (4) a range of technical and management capacities; and (5) an awareness of the multiple agency relationships that are created by the broader financing environment and the provider incentives generated by multiple financing flows.